Morphological Characteristics of Ginseng Leaves in High-Temperature Injury Resistant and Susceptible Lines of Panax ginseng Meyer - Lee, Joon-Soo (The Korean Society of Ginseng, 2011)
Plant leaf cuticle is related to the prevention of moisture loss, transpiration, and diffusion of light reflection. The purpose of this study was to examine the morphological characteristics of ginseng leaves in ginseng plants resistant and susceptible to high temperature injury (HTI) to be related with the leaf-burning. For the HTI resistant lines Yunpoong, high-temperature injury resistance (HTIR) 1, HTIR 2, and HTIR 3, and the HTI-susceptible line Chunpoong, the cuticle densities were 53.0%, 46.2%, 44.9%, 48.0%, and 17.0%; the adaxial leaf cuticle layers were 141.3, 119.7, 119.7, 159.4, and 85.0 nm in thickness; the abaxial leaf cuticle layers were 153.6, 165.8, 157.9, 199.6, and 119.4 nm in thickness; and the stomtal lengths were 21.7, 32.4, 29.4, 30.9, and 21.8 μm, respectively. All of these aspects suggest that HTI resistant lines have higher cuticle density, thicker adaxial and abaxial leaf cuticle layers, and longer of stomta length than the HTI-susceptible line, protecting leaves from moisture loss and excessive transpiration under high temperatures to be resistant against the leaf-burning.